1992
DOI: 10.1246/cl.1992.1905
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption of Palladium(II), Platinum(IV), and Mercury(II) on a New Chitosan Derivative Possessing Pyridyl Group

Abstract: Crosslinked N-(2-pyridylmethyl)chitosan was newly synthesized by crosslinking N-(2-pyridylmethylidene)chitosan of the intermediate compound before reducing it so that the adsorptive activity is not lowered by the crosslinking. The pyridylmethylchitosan selectively adsorbed palladium(II), platinum(IV), and mercury(II) over base metals from hydrochloric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 3 publications
1
20
1
Order By: Relevance
“…They readily form in solution chloropalladate and chloroplatinate anions that can be adsorbed in acidic solutions by protonated amine groups. [32,[35][36][37][38] As previously stated, in HCl solution chitosan is soluble. It is thus necessary to prevent its dissolving by a cross-linking treatment.…”
Section: Platinum and Palladium Sorption -Influence Of Metal Complexamentioning
confidence: 78%
“…They readily form in solution chloropalladate and chloroplatinate anions that can be adsorbed in acidic solutions by protonated amine groups. [32,[35][36][37][38] As previously stated, in HCl solution chitosan is soluble. It is thus necessary to prevent its dissolving by a cross-linking treatment.…”
Section: Platinum and Palladium Sorption -Influence Of Metal Complexamentioning
confidence: 78%
“…The improvement of sorption properties may also consist in grafting other N-bearing groups with acid-base properties compatible with more acidic media. A good example of these modifications is given by the immobilization of pyridyl moieties on chitosan (Baba and Hirakawa 1992;Baba et al 1996Baba et al , 1998Kagaya et al 2000;Justi et al 2004Justi et al , 2005Dhakal et al 2008;Sajomsang 2010). The present study proposes a new route for the synthesis of N-(2-(2-pyridyl)ethyl)chitosan (PEC).…”
Section: Introductionmentioning
confidence: 95%
“…PMC, TMC, and MTPC were synthesized by reducing the Schiff's bases between the primary amino groups of chitosan and the corresponding carboxaldehydes, as described in the previous paper. 4 The intermediate and final products were identified by the IR spectra. The substituted degree was determined to be over 0.9 by using the C/N ratio of an elemental analysis.…”
Section: Reagents and Adsorption Proceduresmentioning
confidence: 99%
“…Recently, we newly synthesized some crosslinked chitosan derivatives available as chelating resins using chitosan. 3,4 We found that new chitosan derivatives (N-(2-pyridylmethyl)chitosan(PMC), N-(2-thienylmethyl)chitosan (TMC),propyl]chitosan(MTPC)) can selectively adsorb precious metals, such as gold(III), palladium(II), and platinum(IV) in hydrochloric acid. 3 We also found that Schiff's base formation is effective in protecting the amino group prior to the crosslinking reaction.…”
mentioning
confidence: 99%